The Tourist Area Life Cycle (TALC) and Its Effect on the Quality-of-Life (QOL) of Destination Community - Uysal, Muzaffer; Woo, E.; Signal, M. (Springer, 2012)
This chapter examines the connection between tourism area life cycle (TALC) and its effects on the quality-of-life (QOL) of destination communities. We posit that as destinations go through structural changes over time, the extent to which the dynamics of change affect the QOL of the resident community varies with the stages of the life cycle. The chapter consists of four major sections. After a brief introduction, the first section presents the concept of TALC and describes the development phases and the indicators that help understand tourism area development. The second section provides a brief discussion on the impact of tourism on the community in relation to TALC, which is then followed by the third section which focuses on the adjustment to change and maintaining the QOL of the community. Section four reviews related literature to support the relation between TALC and QOL of communities. The chapter ends with delineating critical issues for future research, outlining some of the difficulties moving forward, and formulating relevant policy implications that may help the researchers and destination management organizations to further examine the issues that may surround TALC and QOL connections.